1990
DOI: 10.1007/bf01812678
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol reduction with tamoxifen

Abstract: The serum cholesterol levels of 123 consecutively and newly diagnosed women with Stage I and II breast cancer taking tamoxifen were compared with a control group of 81 consecutively newly diagnosed women with Stage I and II breast cancer who were not taking a hormonal treatment or supplement. Other factors that were evaluated were age, menopausal status, tumor size, weight, height, Quetelet index, and smoking and alcohol intake history. The mean cholesterol change in patients on tamoxifen (34.2 +/- 3.6 mg/dl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Based on the cell types and tissues, tamoxifen can function either as an agonist or an antagonist of estrogen receptor (ER) [12]. Tamoxifen also has atheroprotective effects which have been determined in both animal models and humans [13][14][15][16]. We previously reported that tamoxifen increased expression of type BI scavenger receptor (SR-BI), a receptor for high-density lipoprotein, in macrophages isolated from female but not male mice [17].…”
Section: Introductionmentioning
confidence: 97%
“…Based on the cell types and tissues, tamoxifen can function either as an agonist or an antagonist of estrogen receptor (ER) [12]. Tamoxifen also has atheroprotective effects which have been determined in both animal models and humans [13][14][15][16]. We previously reported that tamoxifen increased expression of type BI scavenger receptor (SR-BI), a receptor for high-density lipoprotein, in macrophages isolated from female but not male mice [17].…”
Section: Introductionmentioning
confidence: 97%
“…[17][18][19] Interestingly, Tamoxifen exerts an antagonistic effect on mammary tissues, but adversely acts as an agonist on other tissues such as skeletal 20,21) and cardiovascular systems. [22][23][24] This unexpected discovery provided the impetus for pursuit of tissue-selective agonistic estrogen alternatives, which have beneficial effects on osteoporosis and cardiovascular diseases, and minimal effects on mammary and uterine tissues. Following extensive investigation, novel types of nonsteroidal, estrogen receptor partial agonists, termed as selective estrogen receptor modulators (SERMs), have been identified.…”
mentioning
confidence: 99%
“…Animal and human studies since have attempted to provide biologic evidence to support a cardioprotective effect. It also has been shown that tamoxifen reduces total cholesterol and low-density lipoprotein cholesterol (LDL-C) levels, [13][14][15][16][17][18][19][20][21][22] both of which are known risk factors for coronary artery disease. [23][24][25][26][27] Tamoxifen also reduces circulating levels of lipoprotein(a), 22 which is a potentially more atherogenic lipiprotein than LDL.…”
mentioning
confidence: 99%